The presence of classical Hollywood narration in video games: a study of Grand Theft Auti IV - Mabin, William (My University, 2010)
ABSTRACT: While a film-viewer watches a movie from beginning to end without the ability to manipulate aspects of the environment on screen, video games are constantly being altered through the player’s interaction. Some games however, can be identified as having strong cinematic narratives that detract from varied outcomes and limit game design to a point of closure that cannot be altered. These games have a predetermined script that mimics the formulae used in filmmaking. Typically in game design there are rules that govern what a player is permitted to do within the final product. The presence of these rules form part of what is known as “gameplay”. This research essay is concerned with how such rules can restrict the interactivity of games, limiting them to a linear narrative. This premise will be investigated by applying what Bordwell terms a “classical Hollywood narration” model to an analysis of the game Grand Theft Auto IV (GTA4).